STUDI PENGGUNAAN OBAT PADA PENDERITA DIARE AKUT DI INSTALASI RAWAT INAP BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI – JUNI 2012 - Korompis, Fras; Tjitrosantoso, Heedy; Goenawi, Lily Ranti (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This study aimed to investigate the characteristics with acute diarrhea treated in inpatient installation of BLU RSUP Prof. DR. R. D. Kandou Manado and overview the treatments. This study is a descriptive research and data collection as retrospective for 2 months from November to December 2012 at the Inpatient Installation of BLU RSUP Prof. DR. R. D. Kandou Manado. The study was conducted on 84 records medical records of acute diarrhea. The results show all of the patients used ORS (100 %), but accompanied by the use of other drugs that can help cure the acute diarrhea and treat the other clinical symptoms that accompany acute diarrhea likes fever and vomiting. Additional treatment that used is zinc by 69%, 58% use antipyretics, antiemetics were 27%, 16% use antibiotics and 12 % use probiotics. Keywords : Diarrhea, Acute Diarrhea, Acute Diarrhea Treatments